Strategi Komunikasi Pembelajaran Jarak Jauh Antara Guru dan Siswa Sekolah Menengah Pertama Swasta Granada di Kabupaten Bogor - Catherina Maria; Satya Candrasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
Distance restrictions in order to reduce the number of virus spreads so that they do not increase are the main reason for implementing distance learning programs by utilizing learning technology media. This study aims to find out how the communication strategies used by teachers and students at SMPS Granada, Bogor Regency are as well as the obstacles encountered in distance learning 1during the Covid-19 pandemic.1 The main1 concepts1 used1 are communication strategies,1 communication, 1 distance learning, advantages and disadvantages of online learning, barriers to distance learning and the 1Covid-19 pandemic.1 Interviews were conducted with four resource persons, including teachers and students of SMPS Granada, Bogor Regency. This research shows that teachers and students in teaching and learning activities during the Covid-19 pandemic utilize digital technology media that can help smooth the process of implementing distance learning.